Virus-like particle – mediated delivery of the RIG-I agonist M8 induces a type I interferon response and protects cells against viral infection - Palermo, Enrico; Alexandridi, Magdalini; Di Carlo, Daniele; Muscolini, Michela; Hiscott, John (Frontiers in Cellular and Infection Microbiology, 2022)
Virus-Like Particles (VLPs) are nanostructures that share conformation and self-assembly properties with viruses, but lack a viral genome and therefore the infectious capacity. In this study, we produced VLPs by co-expression of VSV glycoprotein (VSV-G) and HIV structural proteins (Gag, Pol) that incorporated a strong sequence-optimized 5’ppp-RNA RIG-I agonist, termed M8. Treatment of target cells with VLPs-M8 generated an antiviral state that conferred resistance against multiple viruses. Interestingly, treatment with VLPs-M8 also elicited a therapeutic effect by inhibiting ongoing viral replication in previously infected cells. Finally, the expression of SARS-CoV-2 Spike glycoprotein on the VLP surface retargeted VLPs to ACE2 expressing cells, thus selectively blocking viral infection in permissive cells. These results highlight the potential of VLPs-M8 as a therapeutic and prophylactic vaccine platform. Overall, these observations indicate that the modification of VLP surface glycoproteins and the incorporation of nucleic acids or therapeutic drugs, will permit modulation of particle tropism, direct specific innate and adaptive immune responses in target tissues, and boost immunogenicity while minimizing off-target effects.